Estudio de la evolución del diseño publicitario en imprentas del cantón Quevedo año 2018. - Baque Suárez, Ximena Yelitza (2018)
The objective of this research project is based on conducting a study of the evolution of advertising design in the printers of the Quevedo canton in order to demonstrate through the design of a digital magazine that allows to solve the proposal, in which It serves the people in general interested in the graphic arts to be informed of the progress and services offered or printing systems that were available in past times compared to today. It is also based on a map where the location, logo of the printing press and years of trajectory will be recorded in order to recognise the corporate identity that represents them in the market. Despite the fact that there is competition, each printing company has a portfolio of potential clients that are increasing according to the services they offer. For the fulfillment of the objectives of the project, various activities were carried out with the collection of primary information through the visits of fields in which interviews and secondary information were carried out in order to support the proposal as a whole of surveys made to the variety of existing customers in the market. The results obtained allowed to have an idea conception determining several processes for the impression of the advertising design and expectations in the market. The map was made in conjunction with an account in google to generate the key to the App for javascript which is entered an account is discounting money from the card entered at the time of choosing the route of arrival , and the design of the magazine was made in the Corel Draw 2018 program.